基于Gossip通信算法的微网电压不平衡补偿方法 (2017)
本发明提供种基于Gossip通信算法的微网电压不平衡补偿方法，属于微网控制技术领域。该方法通过两个控制层实现，次控制采用本地控制器并通过Gossip算法实现不同DR的不平衡电流均衡控制和实现DR的即插即用功能，二次控制通过集中控制器实现微网电压不平衡度要求。本发明解决了传统不平衡补偿方法电能质量与不平衡电流均衡难兼顾、与电流源控制模式DR难兼容、灵活度低的问题。 The invention provides a microgrid voltage unbalance compensation method based on a Gossip communication algorithm and belongs to the technical field of microgrid control. The method is implemented through two control layers. Primary control achieves unbalance current balancing control of different DRs and plug-and-play functions of the DRs by using uses a local controller and a Gossip algorithm. Secondary control achieves microgrid voltage unbalance degree requirements by means of an integrated controller. The method solves a problem that power quality is difficult to be simultaneously solved with unbalance current balancing, is difficult to be compatible with a current source control mode DR, and is low in flexibility in a conventional unbalance compensation method.